2022
DOI: 10.1128/mbio.03340-21
|View full text |Cite|
|
Sign up to set email alerts
|

IS 26 Veers Genomic Plasticity and Genetic Rearrangement toward Carbapenem Hyperresistance under Sublethal Antibiotics

Abstract: Klebsiella pneumoniae carbapenemases (KPCs) are powerful β -lactamases that enable Gram-negative pathogens to destroy clinically important carbapenems in antibiotic therapies. In particular, KPC-2 is difficult to detect due to a lack of instrument sensitivity in regular laboratory screens, which leads to misdiagnosis and poor treatment outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…IS 26 was regarded as a vital mobile element contributed to the dissemination and rearrangement of resistance determinants, as well as plasmid reorganization ( Harmer and Hall, 2015 ; He et al, 2015 ; Wei et al, 2022 ). A previous study demonstrated that IS 26 was involved in recombination of an IncN1-F33: A-: B- plasmid and an mcr-1 -carrying phage-like plasmid during conjugation process, facilitating the dissemination of mcr-1 ( He et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IS 26 was regarded as a vital mobile element contributed to the dissemination and rearrangement of resistance determinants, as well as plasmid reorganization ( Harmer and Hall, 2015 ; He et al, 2015 ; Wei et al, 2022 ). A previous study demonstrated that IS 26 was involved in recombination of an IncN1-F33: A-: B- plasmid and an mcr-1 -carrying phage-like plasmid during conjugation process, facilitating the dissemination of mcr-1 ( He et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, the genetic rearrangement of a 9,379 bp fragment organized as IS6100-orf3-IS15DI-repB(N)-IS5075-IS26-mph(A) immediately upstream of the tnpA gene and downstream of the tnpR gene, causing the insertion of macrolide resistance determinant containing part IS15DI-repB(N)-IS5075-IS26-mph(A) in the backbone region and the integration of the remnant part of the 2,512 bp fragment between the tnpA gene and the IS15DI, resulting in the formation of Module B. Finally, insertion of the IS26-tet(M)-orf4-tnp-IS5075 element, conferring resistance to tetracyclines, as previously described in pHS13-1-IncHI2 6 https://tool-mml.sjtu.edu.cn/oriTfinder/oriTfinder.html IS26 was regarded as a vital mobile element contributed to the dissemination and rearrangement of resistance determinants, as well as plasmid reorganization (Harmer and Hall, 2015;He et al, 2015;Wei et al, 2022). A previous study demonstrated that IS26 was involved in recombination of an IncN1-F33: A-: Bplasmid and an mcr-1-carrying phage-like plasmid during conjugation process, facilitating the dissemination of mcr-1 (He et al, 2019).…”
Section: Proposed Formation Mechanism Of the Plasmid Pec15-mcr-50mentioning
confidence: 99%
“…First of all, the sequencing bias introduced by library preparation can lead to the gene copy number being over- or underestimated ( 27 ). Second, as CCNE determines the average gene copy number of a clone community or population, it will produce an estimate of less than one gene copy if the bacterial cells in the community lost the gene, especially when the gene is located on a transposon or plasmid ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…39,66 Vaccinia immune globulin intravenous (VIGIV) has also been found useful in treating severe cases of MPX as well as prospective passive antibody-based therapies such as hyperimmune globulin (HIG), monoclonal antibodies (mAbs), and convalescent plasma (CP) have also been suggested to play useful role for treating MPX, particularly beneficial against severe cases. 72 The replicative cycle of MPOX virus in humans and the therapeutic interventions by the anti-MPX viral drugs have been elucidated in Figure . Tecovirimat, which is an orthopoxvirusspecific protein (VP37) inhibitor harbors the…”
Section: Anti-viral Drugs and Therapeutic Interventionsmentioning
confidence: 99%